Javanese Traditional Games in BIPA Learning in the VUCA Era: An Effective Strategy to Improve Language Skills - Kusumaningsih, Dewi; Saptomo, Sri Wahono; Sukarno; Fortuna, Avika Dara; Naimah, Myatun (Proceedings Series on Social Sciences & Humanities, 2024)
This research aims to identify and introduce Javanese traditional games as a tool for BIPA learning in the VUCA (Volatility, Unpredictability, Complexity, and Ambiguity) era to improve the language skills of BIPA learners. The research method used a qualitative research method with a phenomenological approach. Primary data sources include observation of BIPA classes, interviews with BIPA teachers and learners, and documentation of traditional games. Secondary data sources include literature on traditional games, language learning theory, and cultural context analysis in the VUCA era. Data collection was conducted through classroom observation, and interviews with BIPA teaching lecturers and BIPA learners. Data analysis was conducted through thematic techniques to identify themes in the data. The results of the analysis show that traditional Javanese games can improve language skills, creativity, and engagement in BIPA learning. As well as helping to understand culture and social values related to language. Research that introduces Javanese traditional games in BIPA learning is an effective strategy to improve the quality of language learning in the VUCA era. The results of this study are used as a reference for BIPA teachers or BIPA researchers to integrate Javanese traditional games into the BIPA learning process.